"A right to lead": The role of leader legitimacy on group reactions to transgressive leadership. Issue 4 (17th February 2021) - Marques, André G.; Pinto, Isabel R.; Leite, Ana C.; de Moura, Georgina Randsley; van Prooijen, Jan‐Willem; Marques, José M.
Abstract: Research on the transgression credit shows that groups may sometimes turn a blind eye to ingroup leaders who transgress moral norms. Although there is substantial research investigating the underlying criteria of what makes a "good" leader, research often neglects to investigate the role of followers in leader‐group dynamics. In this paper, we offer a novel approach to transgressive leadership by proposing that leader legitimacy is a key factor that determines whether followers' reactions to transgressive leaders are positive or negative. Across two experiments, participants ascribed transgression credit only to transgressive ingroup leaders perceived as legitimate (Studies 1–2, total n = 308). Transgressive illegitimate leaders were viewed as more threatening to the group, were targeted for formal punishment, received less validation for their behavior, triggered negative emotions (anger and shame), and raised higher consensus for their removal from the leadership position than did legitimate leaders. This effect also occurred irrespective of the absence of formal social control measures implemented toward the transgressive leader (Study 2). Mediation analysis showed that leader illegitimacy triggered stronger feelings of group threat and stronger negative emotions which, consequently, fuelled agreement with collective protest against the transgressive leader. Theoretical and practical implications of these findings are discussed.